Impact of N-acetyltransferase 10 on macrophage activation and inflammation-induced cardiac dysfunction - Zilong Xiao; Xiang Wei; Peng Li; Ruizhen Chen; Ziqing Yu; Yixiu Liang; Yangang Su; Junbo Ge (Cell Death and Disease)
Abstract Inflammation-induced cardiac dysfunction, driven by an abnormal immune response, significantly contributes to sepsis-related mortality. Controlling excessive pro-inflammatory cytokine production by immune cells remains a significant challenge. This study investigated the role of N-acetyltransferase 10 (NAT10) in macrophage activation and its contribution to inflammation-induced cardiac dysfunction. Using bone marrow-derived macrophages and an endotoxemia mouse model, we found that NAT10 is significantly upregulated in response to lipopolysaccharide (LPS) due to the deubiquitinating enzyme USP39, which stabilizes the NAT10 protein. ac4C RNA sequencing identified ETS2 as a direct target of NAT10, where the ac4C modification enhanced ETS2 mRNA stability and translation, promoting a pro-inflammatory phenotype in macrophages. NAT10 deficiency reduces LPS-induced macrophage activation and cytokine production, improving cardiac function in mice. Pharmacological inhibition of NAT10 using remodelin produced similar protective effects. Our findings reveal a novel post-transcriptional pathway and highlight the therapeutic potential of targeting NAT10 to mitigate inflammation-induced cardiac injury in endotoxemia